PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (STUDI PADA HOTEL MUTIARA MERDEKA PEKANBARU) - Gusty, Ryndian; Andri, Seno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to analyze organizational culture and organizational commitment and its influence on employee performance of the Mutiara Merdeka Hotel Pekanbaru. Organizational culture as a variabel (X1), organizational commitment as a variabel (X2), and employee performance as a variabel (Y). The method in this research is descriptive quantitative by using SmartPls v.3, where in the sample used are employees of 57 is done, by purposive sampling method and technique of data colection through questionnaires.The results of the analysis using validity test and reliability test. It can be concluded that organizational culture have a significant effect on Employee performance of the Mutiara Merdeka Hotel Pekanbaru judging from the original value of sample estimate of organizational culture on employee performanceis is 0,187 with significant value under 5% as indicated by t-statistic value of 3,209. the positive original value of sample estimate identifies that organizational culture has a positive effect on employee performance through organizational commitment.Keywords : Intervening Variable, SmartPls, Employee Performance.